ВОДНІ РЕСУРСИ КАРПАТСЬКОГО МАКРОРЕГІОНУ: ГЕНЕЗА ПОКРАЩЕННЯ ТА ОХОРОНА - Todoruk, Sergy; Щурик, Михайло (My University, 2019)
У статті розглянуто проблеми використання та відтворення водних ресурсів у Карпатському макрорегіоні. Здійснено аналіз забезпечення макрорегіону водними ресурсами, зазначені проблеми їх використання та збереження. Після проведених досліджень виявлено, що наріжним каменем, на який нині спирається вирішення завдань генези, покращення та охорони водних ресурсів, є діючі засади організації сучасного обліку дебіту води, водокористування та власності на воду. Складність пролягає в тому, що діючі нині законодавчі норми відтворення водоресурсів, їх використання, охорони та поліпшення були сформовані (більшість із них чинні донині) ще в період функціонування командно-адміністративної (директивної) моделі господарювання. Ключова роль при цьому відводиться державним адміністративним органам. Нагальною є потреба запровадження диференційованого підходу при побудові рентної політики в сфері водокористування, в якій визначником податків були би обсяги водозбору, водоспоживання з урахування якості. Аналіз дає можливість стверджувати, що в Україні загалом та Карпатському макрорегіоні зокрема відсутньою донині залишається інформація щодо засад використання води, обсягів споживання, кількісного та якісного стану абсолютної більшості місцевих водних джерел. Аналіз переконує, що використання, збереження, поліпшення та охорона вод на досліджуваній території не відповідає вимогам сучасності, нормативам і правовому забезпеченню країни ЄС. Інтенсифікація антропогенного й техногенного навантаження на природно-ресурсний потенціал, включаючи воду, негативно впливає не лише на зростання водомісткості економіки, а й на погіршення якості води, екологію тощо..
WATER RESOURCES OF THE CARPATHIAN MACROREGION: GENESIS OF ENHANCEMENT AND PROTECTION
The problems of use and reproduction of water resources in the Carpathian macro region are investigated. Provision of macro regions with water resources, problems of their use and conservation has been analyzed. As a result of conducted research it was discovered that the basis on which the solution of the genesis, improvement and protection of water resources is based today are the operating principles of organizing modern accounting of water production, water use and water ownership. The difficulty is that current legislative norms for the reproduction of water resources, their uses, protection and improvement were formed even during the period of operation of the commandadministrative (policy) model of management. The key role is given to the state administrative authorities. The introduction of differentiated approach in constructing a rent policy in the field of water uses in which the determinants of taxes would be the volume of catch, water consumption in consideration of quality is urgent. There is no information about the basis of water uses, consumption volumes, quantitative and qualitative state of the absolute majority of local water sources in Ukraine and the Carpathian macro-region. There has not been a clear legal framework, based on which local self-government bodies could take adequate measures, the introduction of which would create the possibility of legally affecting individuals, legal entities, who not only do not pay for water consumption, but also pollute, pollute, worsen the quality state of another water resource. Carpathian macro-region is one of the richest in Ukraine water. First of all it concerns surface freshwater year, lakes, canals, reservoirs, etc. The analysis convinces that the use, conservation, improvement and protection of water in the studied area does not meet the requirements of the present, norms and legal protection of the EU. Intensification of anthropogenic and technogenic loading on the natural resource potential, including water, affects not only the growth of water economy, but also the deterioration of water quality, ecology, etc.
Keywords: вода; водоресурсний потенціал; водоресурсні джерела; земля; фауна; флора,; охорона; програма; water; earth,; fauna; , flora; protection; program